Aproximación a un plan de negocio para la exportación de uchuva a Canadá (2020)
What will be presented in this work is the approach of a business plan to export the Colombian goldenberry to the Canadian territory, taking into account that it is important to evaluate different conditions of both the market and the sector that can contribute to a good development of the project. Considering what was said before, it was necessary to identify how the cape goose market was in both Colombia and Canada, examining factors such as the demand of Canadian consumers, the supply of goldenberry in Colombia and its export to different parts of the world, what kind of treaty was signed between Colombia and Canada for trade in this type of products; In addition, technical variables of cape goose for export were taken into account, such as its shape, taste, what kind of benefits and types of presentations it has made it so attractive in the Canadian market, or what types of packaging are due use to export it correctly without damaging the product; and last but not least, different strategies were taken into account so that the product in question has the greatest chance of success when doing business, from how to create the company to go to export, to marketing mix strategies to promote the product.